The Influence of Inflation, Interest Rates, and Financial Performance on LQ45 Index Share Prices in 2019-2023 - Jahidah, Nurul; Arraniri, Iqbal; Komarudin, Munir Nur; Fauzan, Adi Ilham (International Journal Administration, Business & Organization, 2024)
This research aims to understand and analyze the effect of inflation on stock prices, the effect of interest rates on stock prices, and the effect of financial performance on stock prices. This study uses a quantitative method. The population in this study consists of companies listed on the Indonesia Stock Exchange and included in the LQ45 index for the years 2019-2023. The sample selection technique used is purposive sampling. Based on predetermined criteria, 21 companies were selected as samples in this study. The data used are secondary data, including inflation data, interest rates, company financial reports, and stock prices. The data collection techniques include non-participatory observation with documentation study and literature review. The data analysis techniques used are descriptive tests, classical assumption tests, panel data regression analyses, and hypothesis testing, with the analytical tool used being EVIEWS 12. The results of the study show that simultaneously, the variables of Inflation, Interest Rates, and Financial Performance have a significant effect on stock prices. Partially, the inflation variable does not affect stock prices, while the interest rate variable has a significant negative effect on stock prices, and financial performance has a significant positive effect on stock prices.